2017
DOI: 10.1177/2050312117719092
|View full text |Cite
|
Sign up to set email alerts
|

Impact of organophosphate exposure on farmers’ health in Kulon Progo, Yogyakarta: Perspectives of physical, emotional and social health

Abstract: Objective:The exposure of organophosphate could be caused by the absorption in some parts of the body like skin and breath. Toxicity may cause nausea, vomiting and dizziness which are not too specific related with the pesticide toxicity. The purpose of this study is to understand the association between organophosphate exposure and farmers’ health in Kulon Progo County from the perspectives of physical, emotional and social health.Methods:This study was conducted using descriptive observational design. The blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…From the results of the study, it was found there were 88% of respondents experiencing acute poisoning which was significantly related to the length of work. [13] A study conducted in Yogyakarta, Indonesia, showed health problems such as tremors in groups of farmers poisoned with organophosphate pesticides [14]. Organophosphate pesticide poisoning can be acute and chronic.…”
Section: Introductionmentioning
confidence: 99%
“…From the results of the study, it was found there were 88% of respondents experiencing acute poisoning which was significantly related to the length of work. [13] A study conducted in Yogyakarta, Indonesia, showed health problems such as tremors in groups of farmers poisoned with organophosphate pesticides [14]. Organophosphate pesticide poisoning can be acute and chronic.…”
Section: Introductionmentioning
confidence: 99%
“…Acute symptoms will appear within 24 h after contact with the insecticide. (7)(8)(9)(10) The chronic organophosphate insecticide poisoning was characterized by distal weakness that occurs 2-4 weeks after exposure. The symptom of chronic poisoning was cramping pain, weakness, fasciculations, twitching and paresthesias of the extremities followed by weakness of the distal limb muscles, especially in the legs.…”
Section: Introductionmentioning
confidence: 99%
“…Cholinesterase inhibitors pesticide (i.e., organophosphates and carbamates) are known to reduce the activity of acetylcholinesterase (AChE) [3]. This will result in the increase of acetylcholine concentration in the synapse which will lead to some nicotinic and muscarinic symptoms and centralperipheral nervous system toxicity [4]. These effects on acetylcholine in synapse could release a high number of glutamate and causing neuronal death because of glutamate excitotoxicity [17].…”
Section: Discussionmentioning
confidence: 99%